Kebijakan Untuk Mencegah Pencurian Data Pribadi Dalam Media Elektronik - Rahayu, Dwi Rani; Nasution, Muhammad Irwan Padli (Jurnal Sains dan Teknologi (JSIT), 2023)
This article discusses the significance of implementing special regulations to maintain the confidentiality of personal data for every citizen as well as implementing strict and comprehensive anti-theft practices through electronic media in Indonesia. This study aims to present an understanding of legal protection against identity theft crimes in cyberspace and the factors that can trigger these crimes. The research method used is normative with reference to library materials in the form of legal materials such as journals, concepts, papers, theories, principles and legal norms currently in force in Indonesia.